2024
DOI: 10.1002/hipo.23610
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hippocampal and retrosplenial cortical spatial and contextual firing patterns

Dev Laxman Subramanian,
Adam M. P. Miller,
David M. Smith

Abstract: The hippocampus (HPC) and retrosplenial cortex (RSC) are key components of the brain's memory and navigation systems. Lesions of either region produce profound deficits in spatial cognition and HPC neurons exhibit well‐known spatial firing patterns (place fields). Recent studies have also identified an array of navigation‐related firing patterns in the RSC. However, there has been little work comparing the response properties and information coding mechanisms of these two brain regions. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 102 publications
1
5
0
Order By: Relevance
“…Previous studies have documented the spatial firing properties of RSC neurons as rats traversed the maze during continuous alternation (Miller et al, 2019; Subramanian et al, 2024) and similar spatial firing patterns were observed here (see examples in Fig. 2A).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Previous studies have documented the spatial firing properties of RSC neurons as rats traversed the maze during continuous alternation (Miller et al, 2019; Subramanian et al, 2024) and similar spatial firing patterns were observed here (see examples in Fig. 2A).…”
Section: Resultssupporting
confidence: 85%
“…However, the range of lesion placement did not allow systematic examination of the role of individual subregions. Our previous studies of RSC neuronal firing patterns (Subramanian et al, 2024) suggest a distributed coding scheme with little evidence of specialization along the rostro-caudal extent of the RSC (but see Pothuizen et al, 2009; Trask et al, 2021; Van Groen et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations